Enhancing Bilateral Cooperation: Indonesia-Russia Defense Relations - Manurung, Hendra (JASSP, 2021)
This research aims to elaborate further on Indonesia and Russia bilateral cooperation by utilizing defense relations in the Southeast Asia region. Indonesia’s defense cooperation with Russia is a strategy of sustaining foreign and defense policy instruments abroad to achieve interests and protect national sovereignty. This study uses a descriptive analysis of qualitative approach, and done through literature-based relating to the problems that arise. Additionally, journals, related documents, and websources are also used as supporting data. It employs neorealism approach in understanding bilateral defense relations. Thus, by strengthening Indonesian defense diplomacy, how Indonesia national interests is able to pursue closer defense cooperation with Russia, and how this collaborationcontributes to Indonesian defense diplomacy regionally in encountering external threat. However, through the ASEAN Defense Ministerial Meeting and the ASEAN Regional Forum, Indonesia’s defense diplomacy utilized strategy which aim to generating mutual confidence, and reducing potential threats that can arise from the external threat. Indonesia, so far, has utilized its defense diplomacy by intensifying defense cooperation with Russia to foster a sense of mutual trust and enhancement effort in national defense capabilities to anticipate any potential external security threats. Indonesia’s effort to enhance its regional power reputation for implementing foreign and defense policy at the international level, particularly at upgrading its national defense system. This research revealed that by strengthening economic cooperation and defense diplomacy, Indonesia would secure its defense cooperation with Russia and vice versa. As the most populous Muslim nation, Indonesia, 3rd world largest democraciesand significant regional power, intentionally has a strategic interest in maintaining peace and stability.